(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Using alternative materials, which have better engineering quality than traditional materials and are more cost-effective, has received a lot of attention recently. One of the most crucial components in many building projects, such as earth canals and earth dams, is soil. The fact that soil might offer all the resistant qualities required for a project highlights the value of several techniques used to enhance soil quality. The vast majority of construction projects employ clay soil. Because clay soils, especially soft clay soils, have good plastic qualities, their shear strength, compressive strength, and volume changes decrease as moisture content rises. Structures generally suffer permanent harm as a result of these issues, which emphasises how crucial soil improvement is. The use of such refuse and industrial wastes and their subsidiary products as alternatives to construction materials may effectively contribute to environmental preservation and minimize their negative effects on the Environment, especially in light of the millions of tonnes of waste produced annually across the nation, which not only poses the problem of disposal but also adds to environmental contamination and health risks. In the current study, eggshell powder was utilized as a waste to mix with soil in order to examine clay soil’s index characteristics, compaction, and shear strength at various mixed proportions. The shear strength of soils that had already been tested was then contrasted with experimental specimens that had been combined with various ratios of eggshell powder.